Pilot study of sources and concentrations of size-resolved airborne particles in a neonatal intensive care unit. (September 2016) - Bhangar, Seema; Brooks, Brandon; Firek, Brian; Licina, Dusan; Tang, Xiaochen; Morowitz, Michael J.; Banfield, Jillian F.; Nazaroff, William W.
Abstract: Infants in neonatal intensive care units (NICUs) are vulnerable to environmental stressors. Few studies have reported on airborne particles in the NICU environment. During a four-day pilot study in a private-style NICU, we measured size-resolved particle number (PN) concentrations with 1-min resolution. The investigation included simultaneous sampling in an unoccupied baby room and in an incubator of an otherwise normally functioning NICU. Background submicron (0.3–1 μm) particle levels in the room were 3–4 orders of magnitude lower than outdoors, owing to high-efficiency particulate filtration of supply air. Airborne supermicron particles were detected in the room; their presence was attributed primarily to emissions from occupant movements. The fraction of in-room PN detected within an infant incubator ranged from 0.2 for particles >10 μm to 0.6 for particles with diameter 0.3–0.5 μm. The incubator humidifier was a strong additional source of particles smaller than 5 μm. Activities by researchers, designed to simulate caregiver visits, were associated with elevated particle concentrations across all measured size ranges, and were particularly discernible among larger particles. Concentrations increased with the number of occupants and with the duration and vigor of activities. The highest levels were observed when fabrics were handled. Against the low background in this environment, even small occupancy-associated perturbations – such as from a brief entry – were discernible. Measurements from a second NICU in a different US region were found to be broadly similar. A notable difference was higher submicron particle levels in the second NICU, attributed to elevated outdoor pollution. Highlights: We study size-resolved particle number concentrations in a NICU room and incubator. Presence of airborne supermicron particles is mainly attributed to human emissions. Concentrations increase with the number of occupants and vigor of their activities. Concentrations within incubator are a substantial fraction of those in room air. Incubator humidifier is a source of airborne particles smaller than 5 μm.